SCHOOLING OF RURAL WORKERS: CHALLENGES AND OPPORTUNITIES FOR THE GUARANTEE OF RIGHTS TO EDUCATION - Vieira, Alicia Rosalva Barbosa; Bereta, Thaísa Angélica Déo da Silva; de Mello, Isadora da Rocha Spinola (Seven Editora, 2024)
Studies state that the need to work is the main reason given by young people aged 14 to 29 to drop out of school. In this way, Youth and Adult Education (EJA) is a teaching modality whose objective is to ensure the educational rights of the population that did not have access to or interrupted their studies before the end of Basic Education. The present research aims to historically understand the challenges and perspectives of rural workers' access to educational programs. First, the literature review was adopted as a method, from 2007 to 2023, on the topic of schooling of rural workers. Two rural workers enrolled in EJA also participated, through a semi-structured interview. The interviewees pointed out that fatigue was the main factor that prevented the continuity of studies, and the EJA teaching modality was beneficial for school education. Brenner and Carrano (2023) highlight that work and school are social spaces and times that, when articulated, produce expectations and make life projects viable, and work should not only be understood as a search for means of subsistence, but also as the search for independence and autonomy on the part of students. There are several challenges in reconciling study and work, raising reflections on the importance of schooling and the contributions of Psychology to the understanding of the psychological processes necessary for the formation of the subject, the educational process and the implementation of educational activities. DOI:https://doi.org/10.56238/sevened2024.033-014